Credit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
There is considerable disagreement about the value of credit, particularly over whether the ?poorest of the poor? are likely to benefit from it. This disagreement is reflected in the interviews of this pack.